2021
DOI: 10.14336/ad.2020.0708
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Schwann Cell Aging: Implications for Age-Associated Neuromuscular Dysfunction

Abstract: Action potential is transmitted to muscle fibers through specialized synaptic interfaces called neuromuscular junctions (NMJs). These structures are capped by terminal Schwann cells (tSCs), which play essential roles during formation and maintenance of the NMJ. tSCs are implicated in the correct communication between nerves and muscles, and in reinnervation upon injury. During aging, loss of muscle mass and strength (sarcopenia and dynapenia) are due, at least in part, to the progressive loss of contacts betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 333 publications
(468 reference statements)
0
21
0
Order By: Relevance
“…For both termini, the axon branches from peripheral bundles toward specific cellular targets, to form morphologically distinct connections. The axons leading to NMJs are myelinated [31], whereas the more distal pre-synaptic terminal is unmyelinated [32]. mSCs are found in/on the myelinated region of the NMJ axon, and nmSCs (important for maintaining synapses [32]) are found at the terminal, which are called terminal SCs (tSCs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For both termini, the axon branches from peripheral bundles toward specific cellular targets, to form morphologically distinct connections. The axons leading to NMJs are myelinated [31], whereas the more distal pre-synaptic terminal is unmyelinated [32]. mSCs are found in/on the myelinated region of the NMJ axon, and nmSCs (important for maintaining synapses [32]) are found at the terminal, which are called terminal SCs (tSCs).…”
Section: Resultsmentioning
confidence: 99%
“…The axons leading to NMJs are myelinated [31], whereas the more distal pre-synaptic terminal is unmyelinated [32]. mSCs are found in/on the myelinated region of the NMJ axon, and nmSCs (important for maintaining synapses [32]) are found at the terminal, which are called terminal SCs (tSCs). In adipose, the NAN similarly branches from myelinated nerves with the terminal itself being unmyelinated, and like the NMJ, the NAN is immediately preceded by SCs.…”
Section: Schwann Cells In Subcutaneous Adipose Tissuementioning
confidence: 99%
“…To date, it has been consistently reported that with aging comes a decreased capacity for terminal sprouting in peri-synaptic Schwann cells, as well as heightened sensitivity to inflammation of those same cells, leading to the diminished regenerative capacity of aging neurons [ 16 , 81 ]. Moreover, 80% of aged endplates are no longer in contact with peri-synaptic Schwann cells, while only about 20% of aged NMJs are fully capped by those glial cells as they are in young adult synapses [ 16 , 82 ]. Those peri-synaptic Schwann cells that are seen at aged NMJs typically exhibit unusually thin, disorganized terminal branches/sprouts.…”
Section: Effects Of Aging On the Nmjmentioning
confidence: 99%
“…Each muscle fiber has a specialized post-synaptic area in which nicotinic AchRs (nAchR) are clustered, forming a characteristic Pretzel-like structure that will interact with the motor nerve ending. However, besides the MNs and muscle fibers, Terminal Schwann Cells (TSC) and the recently discovered kranocytes are also components of the NMJ [ 283 , 284 ]. TSCs are close to the nerve terminal and are essential to detect and modulate synaptic communication, regulate NMJ stability, and oversee NMJ repair [ 285 , 286 ].…”
Section: The Neuromuscular Junction In Alsmentioning
confidence: 99%